Analysis of Eco Literacy, Environmental Concern, Perception Towards The Behavior of MSMEs in Kudus Regency in Implementing Green Economy - Risnawati, Heni; Puspa Ningrum, Nurani; Kumala Wulandari, Hilda (Islamic Accounting Journal, 2025)
Objective & object: Increasing population growth requires effective management of natural resources. Scarcity of natural resources provides awareness to the community with responsible resource management and also considers the environment. This study aims to determine the effect of Eco Literacy, Environmental Concern and Perception on the behavior of MSMEs in Kudus Regency in the Implementation of Green Economy. Methods: The sample in this study was 41 using purposive sampling technique, namely MSMEs engaged in the field of food and beverage production. The data used are primary data by distributing questionnaires. Data analysis used in this study is using multiple linear regression analysis with the help of SPSS. Results & Conclusions: The results of the study show: 1) there is no significant effect of Eco Literacy on behavior in the implementation of Green Economy. 2) there is a significant effect of Environmental Concern and perception on behavior in the implementation of Green Economy. 3) simultaneously between the variables Eco Literacy, Environmental Concern and Perception have a very significant effect on the green economy of MSMEs in Kudus Regency. Limitations: The limitation in this study is the small number of respondents. Data collection by questionnaire so that respondents’ answers are limited to only providing answers to statements in the questionnaire. Implications: The results of this study are expected to contribute to MSMEs to further implement environmentally friendly business activities in realizing the implementation of a green economy. Keywords: Eco literacy , Concern environment , UMKM perception , Green economy .